Magnolol additive improves carcass and meat quality of Linwu ducks by modulating antioxidative status. (15th November 2019) - Lin, Qian; Peng, Simin; Li, Yinghui; Jiang, Guitao; Liao, Zhenzhang; Fan, Zhiyong; He, Xi; Dai, Qiuzhong
Abstract: Magnolol rich in Magnolia officinalis is a bioactive polyphenolic compound. The aim of this study was to clarify the effects of magnolol additive (MA) on carcass and meat quality, biochemical characteristics and antioxidative capacity of Linwu ducks, by comparing it to that of antibiotic additive (colistin sulphate, CS). A total of 275 49‐d‐old ducks were randomly assigned to 5 groups with 5 cages of 11 ducks each and fed by the diets supplemented with 0, 100, 200 and 300 mg of MA/kg and 30 mg of CS/kg for 3 weeks, respectively. The results revealed that MA administration not only increased dressed percentage (calculated as a percentage of live weight), percentage of breast muscle, leg muscle and lean meat (calculated as a percentage of eviscerated weight), but also remarkably increased a*45 min and pH45 min of leg muscle. Moreover, MA administration decreased the percentage of abdominal fat (calculated as a percentage of eviscerated weight), 45‐min cooking loss, water loss rate of leg muscle, 45‐min cooking loss and drip loss of breast muscle at 24 hr and 48 hr. Furthermore, MA administration enhanced the activities of superoxide dismutase and catalase in serum or liver, serum total antioxidant capacity and hepatic reduced glutathione concentration significantly, compared with the basal diet or CS group ( p  < .05). On the other hand, triglyceride, total cholesterol, aspartate aminotransferase, malondialdehyde, protein carbonyl and 8‐hydroxy‐2'‐deoxyguanosine contents in serum and liver were significantly increased in Linwu ducks fed with CS, compared with MA groups ( p  < .05). Taken together, these data demonstrated that magnolol could effectively improve the carcass and meat quality of Linwu ducks by regulating the in vivo antioxidant status and would be a potential candidate to replace antibiotic.